2002
DOI: 10.1111/j.1349-7006.2002.tb01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Formulations for Effective Administration of Lipophilic Malonatoplatinum(II) Complexes

Abstract: Due to the lipophilicity of the malonatoplatinum complexes, the entrapment efficiency of drugs within the liposomes was over 90% except for the AM complex, and platinum drug stability was also satisfactory ( > > > >90%) in these liposomal systems. In vitro cytotoxicity was tested in human ovarian carcinoma cells sensitive (A2780) and resistant to cisplatin (A2780/PDD). In both cell lines, the liposomal DBM complex was much more cytotoxic than the corresponding DAM and ABM complexes, which means that the more h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The addition of DMPG in the lipid mixtures for liposomes preparation has been performed to prevent aggregation, to reduce physical degradation of the vesicular structures (New, 1990), or to enhance electrostatic interactions with positively charged molecules (Were et al, 2003). Since there was no report on using liposomes prepared with DMPG to entrap Cur but only other lipophilic drugs (Han et al, 2002;Sampedro et al, 1994), the liposomes with different phospholipids (DMPG:DMPC) and cholesterol ratio were produced to evaluate the suitability of the liposome formulations for Cur loading. From Table 2, it can be observed that the liposome size was between 100 and 300 nm, except for A0 and B0 formulae, which their size distribution was highly scattered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of DMPG in the lipid mixtures for liposomes preparation has been performed to prevent aggregation, to reduce physical degradation of the vesicular structures (New, 1990), or to enhance electrostatic interactions with positively charged molecules (Were et al, 2003). Since there was no report on using liposomes prepared with DMPG to entrap Cur but only other lipophilic drugs (Han et al, 2002;Sampedro et al, 1994), the liposomes with different phospholipids (DMPG:DMPC) and cholesterol ratio were produced to evaluate the suitability of the liposome formulations for Cur loading. From Table 2, it can be observed that the liposome size was between 100 and 300 nm, except for A0 and B0 formulae, which their size distribution was highly scattered.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of DMPG in accelerating SF gelation were investigated and the obtained hydrogels were used for cell encapsulation. Also, DMPG can be a component for the preparation of liposomes (Li et al, 2015), which were used for the entrapment of lipophilic molecules in combination with a zwitterionic phospholipid, 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) (Han et al, 2002;Sampedro et al, 1994). Therefore, DMPG-based liposomes were prepared to function as a delivery system of curcumin and an inducer of SF gelation.…”
Section: Introductionmentioning
confidence: 99%
“…19 Briefly, the platinum(II) complexes were obtained by reaction of the corresponding ligands with potassium tetrachloroplatinate(II) in a water/methanol mixture at room temperature for 24 h, and were isolated by simple filtration. The results of the characterization of these complexes by elemental analyses, infrared spectroscopy and 1 H, 13 C and 195 Pt NMR spectroscopy have been presented in our previous work. 19 The purity of the compounds was confirmed by elemental analyses.…”
Section: Synthesis Of Platinum Complexesmentioning
confidence: 99%
“…11 The encapsulation of lipophilic derivatives of cisplatin in liposomes has been explored to allow for the safe parenteral administration of these complexes. [12][13][14] In addition to their solubilization properties, liposomes have been extensively studied for the passive and active targeting of drug to tumors. 15 For instance, the use of polyethylene glycol as PEG-coated liposomes was found to prolong the circulation time of liposomes in blood, to passively enhance their tumor localization, and improve the therapeutic efficacy of platinum complexes, exploring the EPR (enhanced permeability and retention) effect.…”
Section: Introductionmentioning
confidence: 99%